Surface Engineering towards Self-Cleaning Applications: Laser Textured Silicon Surface. (2017) - Yilbas, Bekir Sami; Keles, Omer; Toprakli, Abdurrahman Yagmur
Abstract: Surface finishing of parts plays a critical role in engineering applications. Although the efforts towards improving surface finish have been made over the past decades, the recent developments in science and technology accelerate the progresses made towards superior surface characteristics. Tailoring the physical and chemical characteristics of the surfaces enable to extend the surface engineering studies in many new fields including medical, biological, environmental engineering, and architecture. The current interest in self-cleaning of surfaces for energy applications, such as solar thermal and solar photovoltaic energy harvesting, makes the surface finish as one of the hot topics of the research. In the present study, laser texturing of silicon surface is presented in line with the self-cleaning characteristics. It is found that laser texturing gives rise to hydrophobicity characteristics at the surface because of: i) micro/nano size pillars, and ii) nitride phase formed at the surface.